Gravitational wave memory in ΛCDM cosmology. (28th September 2017) - Bieri, Lydia; Garfinkle, David; Yunes, Nicolás
Abstract: We examine gravitational wave memory in the case where sources and detector are in a ΛCDM cosmology. We consider the case where the Universe can be highly inhomogeneous, but gravitational radiation is treated in the short wavelength approximation. We find results very similar to those of gravitational wave memory in an asymptotically flat spacetime; however, the overall magnitude of the memory effect is enhanced by a redshift-dependent factor. In addition, we find the memory can be affected by lensing.